Healthy Living Lifestyles: Land and Sea: FS441/FSHN22-7, 5/2022 - Farzad, Razieh; Scharf, Brittany; Davis, Jim E.; Duncan, LuAnn; Anderson, Jana (EDIS, 2022)
This new 5-page publication of the UF/IFAS Food Science and Human Nutrition Department provides information for the general public about the benefits of incorporating land- and water-based natural resource activities to achieve a healthy lifestyle. Written by Razieh Farzad, Brittany Scharf, Jim E. Davis, LuAnn Duncan, and Jana Anderson. https://edis.ifas.ufl.edu/fs441